2021
DOI: 10.1371/journal.ppat.1009441
|View full text |Cite
|
Sign up to set email alerts
|

Viral infection of human neurons triggers strain-specific differences in host neuronal and viral transcriptomes

Abstract: Infection with herpes simplex virus 1 (HSV-1) occurs in over half the global population, causing recurrent orofacial and/or genital lesions. Individual strains of HSV-1 demonstrate differences in neurovirulence in vivo, suggesting that viral genetic differences may impact phenotype. Here differentiated SH-SY5Y human neuronal cells were infected with one of three HSV-1 strains known to differ in neurovirulence in vivo. Host and viral RNA were sequenced simultaneously, revealing strain-specific differences in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 105 publications
(203 reference statements)
1
27
0
Order By: Relevance
“…HSV-1 F and KOS strain were originally isolated from facial lesions and exhibited lower mortality in comparison to clinical HSV-1strains ( Dix et al, 1983 ). Besides, F and KOS strain demonstrated different transcriptional changes and viral gene or protein expression patterns in infected human neuronal cells, whereas no difference in infected epithelial cells ( Mangold et al, 2021 ). Accordingly, we examined the antiviral activity against ACV-resistant HSV-1 strains in epithelial Vero cells.…”
Section: Resultsmentioning
confidence: 99%
“…HSV-1 F and KOS strain were originally isolated from facial lesions and exhibited lower mortality in comparison to clinical HSV-1strains ( Dix et al, 1983 ). Besides, F and KOS strain demonstrated different transcriptional changes and viral gene or protein expression patterns in infected human neuronal cells, whereas no difference in infected epithelial cells ( Mangold et al, 2021 ). Accordingly, we examined the antiviral activity against ACV-resistant HSV-1 strains in epithelial Vero cells.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of ICP0 alone was necessary and sufficient to trigger apoptosis during HEp-2 cells infection by HSV-1 [ 234 ]. A new study presented by Mangold et al [ 235 ] showed that HSV-1 modulates viral gene expression and protein levels, depending on the viral strain in infected human neuronal cells. In turn, infected neurons change the response pathways to different HSV-1 strains and activate genes involved in death receptor signaling and retinoic acid-mediated apoptosis signaling.…”
Section: Apoptosis and Autophagymentioning
confidence: 99%
“…In turn, infected neurons change the response pathways to different HSV-1 strains and activate genes involved in death receptor signaling and retinoic acid-mediated apoptosis signaling. Furthermore, the changes included pathways that regulate neuronal cell adhesion, migration, and cytoskeletal rearrangement (pathways associated with integrin signaling, integrin-linked kinase (ILK), ephrin B-, and ephrin receptor-signaling), as well as the regulation of neuronal adherens junction components in response to particular HSV-1 strains [ 235 ].…”
Section: Apoptosis and Autophagymentioning
confidence: 99%
“…The post-transcriptional stability and, thereby, viral and cellular RNA levels are regulated by the nuclease activity of the aptly named virion host shutoff (VHS) protein, further complicating conclusions of transcriptional regulation from the level of total, cytoplasmic, or polyadenylated RNA. While recent studies have identified many interesting findings from total RNA analysis [131][132][133][134][135], general conclusions at the level of transcription are complicated by the varying technical methods and biological contexts utilized. Interestingly, nuclease activity of VHS globally reduced Pol II transcription of host genes, as was observed before with the SOX nuclease from murine gamma-herpesvirus 68 (MHV68) [111,136].…”
Section: Broader Network and Future Considerationsmentioning
confidence: 99%